Personal Recovery as a Protective Factor Against Suicide Ideation in Individuals With Schizophrenia. Issue 11 (November 2016) - Jahn, Danielle R.; DeVylder, Jordan E.; Drapalski, Amy L.; Medoff, Deborah; Dixon, Lisa B.
Abstract : Abstract: Suicide rates are elevated in individuals with schizophrenia, yet evidence is mixed regarding the roles of positive and negative symptoms as risk factors for suicide in this population, suggesting that there may be other influential variables. One such variable may be personal recovery. Therefore, the purpose of this study was to test the hypothesis that personal recovery would moderate the relationship between symptoms of schizophrenia and suicide ideation. This hypothesis was tested in a sample of 169 individuals diagnosed with schizophrenia or schizoaffective disorder using a Poisson regression model. Results suggested that there was no significant interaction between recovery and symptoms of schizophrenia. However, recovery was a significant predictor of suicide ideation after controlling for psychiatric symptoms. These findings indicate that recovery is associated with lower suicide ideation and thus may protect against it. Thus, recovery should be assessed, and potentially intervened upon, to reduce suicide risk in individuals with schizophrenia.